Islamic Human Development Index (i-HDI) and Poverty Reduction in OIC Countries - Shirazi, Nasim; Md Isa, Maizura; Abdul Kareem, Mohamed Ariff; Eskandar Shah, Mohamed Eskandar Shah (Journal of King Abdulaziz University: Islamic Economics, 2023)
Focus on poverty requires a broader perspective than just concentrating on the issue of insufficient income. Thus, the adoption of human development strategies is pertinent for poverty reduction. It inspires a widening of the informational base on poverty by investigating the deprivation of functioning and capabilities of a human being. United Nations Development Programme (UNDP) has developed the Human Development Index (HDI) which can be considered the most comprehensive indicator. However, it is not fully compatible and sufficient for measuring human development from the Islamic perspective. In this study, we develop the Islamic human development index (i-HDI) based on the five pillars of the Maqasid Shariah framework; preservation of Ad-Din (faith), preservation of An-Nafs (life), preservation of Al-Aql(intellect), preservation of An-Nasl (posterity), and preservation of Al-Mal ( wealth). Also, we test the effects of (i-HDI) on poverty reduction by employing panel regression and index construction techniques. Our findings show that the elements of Islamic human development are significantly relevant to poverty reduction and could be used as an alternative to HDI. As a result, our research adds further insight to this perennial problem, enabling more effective strategies and initiatives, especially for the Muslim world.